2020
DOI: 10.1371/journal.pone.0243364
|View full text |Cite
|
Sign up to set email alerts
|

Increase in longevity and amelioration of pesticide toxicity by natural levels of dietary phytochemicals in the honey bee, Apis mellifera

Abstract: For the past decade, migratory beekeepers who provide honey bees for pollination services have experienced substantial colony losses on a recurring basis that have been attributed in part to exposure to insecticides, fungicides, or their combinations applied to crops. The phytochemicals p-coumaric acid and quercetin, which occur naturally in a wide variety of bee foods, including beebread and many types of honey, can enhance adult bee longevity and reduce the toxicity of certain pesticides. How variation in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 95 publications
(68 reference statements)
1
10
0
Order By: Relevance
“…Similarly, the reduced mortality risk upon exposure to pesticide was observed over a range of relatively low natural concentrations (5, 50 and 500 µM) for p-coumaric acid. Higher concentrations (1000 µM) increased or did not change the toxicity of pesticides [45]. Our results are, therefore, consistent with these royalsocietypublishing.org/journal/rsos R. Soc.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similarly, the reduced mortality risk upon exposure to pesticide was observed over a range of relatively low natural concentrations (5, 50 and 500 µM) for p-coumaric acid. Higher concentrations (1000 µM) increased or did not change the toxicity of pesticides [45]. Our results are, therefore, consistent with these royalsocietypublishing.org/journal/rsos R. Soc.…”
Section: Discussionsupporting
confidence: 91%
“…The pollen-induced differences in pesticide sensitivity reported in our study could not be explained by this nutritional factor since both pollen diets had similar P : Ls. However, several studies have shown that the pollen phytochemicals quercetin and p-coumaric acid, upon ingestion, can significantly enhance bee longevity [46,104] and also tolerance to several pesticides [45][46][47]. However, the effects of these phytochemicals are concentration-dependent; lower concentrations tend to have a positive effect on honeybee longevity ( p-coumaric acid at 5, 50 and 500 µM and quercetin at 12.5, 25 and 250 µM), while higher natural concentrations (1000 µM) have no effects [45,46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19,20 In addition to protein content, pollen contains a variety of necessary lipids, essential fatty acids, 21−23 and a broad diversity of bee health-modulating bioactive compounds, such as vitamins and phenolic acids. 24,25 Thus, there are opportunities to enhance feed to more closely mimic the chemical composition of pollen, especially to serve the growing demands of a majority of US beekeepers who feed supplemental nutrition to their colonies. 20 Importantly, given the challenges of feeding the world's human population, sustainable ingredients that do not compete with human food production are good candidates to address this crucial need of modern beekeeping.…”
Section: Introductionmentioning
confidence: 99%